Sexile as a Narrative Motif in Three Stories from Mundo cruel (2010), by Luis Negrón - Monge Gómez, Bernal (2025)
One of the trends in contemporary Latin American literature seeks, among other purposes, to make visible the subjects and bodies that the official discourse relegated to the condition of the other. In this context, the Puerto Rican case is fundamental, because recent textual practices seek to function not only as an aesthetic object, but also as a political act reclaiming that otherness. An example of this is the queer theme, which has gradually appropriated the Puerto Rican narrative to make dissident sexualities visible from the perspective of different characters. This article analyzes sexile as a narrative motif in the discursive construction of homophobia in the stories “Junito”, “Muchos o de cómo a veces la lengua es bruja” and “Mundo cruel”, published in Mundo cruel (2010), by Luis Negrón. It is concluded that the United States represents an ideal space to experience sexuality or a place far from the national territory, where those, the inverted, should go. In Puerto Rico, migration is, therefore, necessary: ​​for some, because it allows the experience of sexuality in freedom; for others, because it maintains the status quo of the nation.